Reduced Programming Time and Strong Symptom Control Even in Chronic Course Through Imaging-Based DBS Programming - Lange, Florian; Steigerwald, Frank; Malzacher, Tobias; Brandt, Gregor Alexander; Odorfer, Thorsten Michael; Roothans, Jonas; Reich, Martin M.; Fricke, Patrick; Volkmann, Jens; Matthies, Cordula; Capetian, Philipp D. (Frontiers in Neurology, 2021)
Objectives: Deep brain stimulation (DBS) programming is based on clinical response testing. Our clinical pilot trial assessed the feasibility of image-guided programing using software depicting the lead location in a patient-specific anatomical model. Methods: Parkinson’s disease patients with subthalamic nucleus-DBS were randomly assigned to standard clinical-based programming (CBP) or anatomical-based (imaging-guided) programming (ABP) in an 8-week crossover trial. Programming characteristics and clinical outcomes were evaluated. Results: In all 10 patients, both programs led to similar motor symptom control (MDS-UPDRS III) after four weeks (medicationOFF/stimulationON; CPB: 18.27±9.23; ABP: 18.37±6.66). Stimulation settings were not significantly different, apart from higher frequency in the baseline program than CBP (p=0.01) or ABP (p=0.003). Time spent in a program was not significantly different (CBP: 86.1±29.82%, ABP: 88.6±29.0%). Programing time was significantly shorter (p=0.039) with ABP (19.78±5.86 min) than CBP (45.22±18.32). Conclusion. Image-guided DBS programming in PD patients drastically reduces programming time without compromising symptom control and patient satisfaction.